Economic Valuation of Tourist Attractions in Luan Prabang: An Application of the Contingent Valuation Method - lorvanin, somephone; CHANTHAVONE, Thongphanh; POUNALEE, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Tourism serves as a vital driver of socio-economic development in Luang Prabang City, Lao PDR. This study evaluates the economic value of selected tourism attractions across three major categories: natural tourism (Kuang Si Waterfall), historical tourism (the Luang Prabang National Museum), and cultural tourism (Phousi Mountain). Employing economic valuation approaches, the study estimates tourists' willingness to pay (WTP) for entrance fees to these attractions. The findings are intended to inform sustainable tourism management and to support the long-term conservation and preservation of these heritage resources for the benefit of Lao society and future generations. The results revealed that, for natural tourism attractions, domestic tourists expressed a WTP of 39,374.97 Lao Kip per person per visit, while international tourists expressed a WTP of 47,938.42 Lao Kip per person per visit. Regarding historical tourism attractions, domestic tourists were willing to pay 11,234.66 Lao Kip per person per visit, compared to 69,974.35 Lao Kip per person per visit among international tourists. With respect to cultural tourism attractions, domestic tourists indicated a WTP of 52,812.86 Lao Kip per person per visit, whereas international tourists were willing to pay 45,858.48 Lao Kip per person per visit toward their preservation and sustainable management. These findings provide a quantitative basis for policymakers and tourism authorities to establish appropriate entrance fee structures that balance visitor accessibility with the financial requirements of heritage conservation